A Comparative Evaluation of Priming With Midazolam And Propofol on Induction Dose Requirement of Propofol In Patients Undergoing Surgery Under General Anaesthesia - Nigam, Ankita; Verma, Neeta; Singam, Amol (International Journal of Psychosocial Rehabilitation, 2020)
The concept of priming and autocoinduction and coinduction is well known and better than monotherapy. Here we compare priming with midazolam and propofol on inducing dose of propofol. To find whether each of the drugs- Midazolam, and Propofol is effective in reducing the induction dose of Propofol. Methodology: In this prospective observational study where 60 patients are divided into two groups. group A recieved inj propofol 0.5mg/kg iv followed by remaining dose of propofol 2mg/kg for induction of GA. Group B recieved inj. midazolam 0.05mg/kg followed by propofol 2mg/kg. we will compare total dose of propofol required for induction taking loss of verbal contact as the end point. Haemodynamic stability will also be compared. we hypothesize that when midazolam is used with propofol then induction dose of propofol is reduced. When the result will come as expected then we can conclude that concept of priming is better than monotherapy and overall induction dose of propofol will be reduced. hence it will reduce the adverse effects of propofol and it will be cost effective as well.